Addition of Sildenafil in Patients with Pulmonary Arterial Hypertension with Inadequate Response to Bosentan Monotherapy - Nancy R Porhownik; Hassan Al-Sharif; Zoheir Bshouty (Canadian Respiratory Journal)
BACKGROUND: Pulmonary arterial hypertension (PAH) remains a progressive disease despite improvement when using one of three medication classes: prostanoids, endothelin receptor antagonists or phosphodiesterase-5 inhibitors. Combination therapy has been proposed for patients with unsatisfactory response to monotherapy.